Equipment Leasing as a Source of Finance For Small and Medium Scale Entrepreneurs In Nigeria - Eniola Sule , Olatunji; Iyabo Amuni , Sarat (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
The paper is looking into fund raising through leasing of equipments and machineries rather than purchasing them on cash and carry basis as such having much impact and impart on the working capital of the small and medium scale enterprises. The paper looked into relevant and related studies and came up with the ideas like concept of leasing, types of lease arrangement and Central Bank of Nigeria regulations as to lease for small and medium scale enterprises. The study made use of a self designed questionnaire called ELESOF to get information from respondents and came up with certain conclusions that equipment leasing is very paramount to the survival of organisations and that though the CBN gave the rules to encourage of small and medium scale enterprises through equipment leasing via the commercial banks but this is just an illusion as far as the instruction by CBN to commercial banks.